Exploring the challenges of virtual internships during the COVID-19 pandemic and their potential influence on the professional identity of health professions students: A view from Qatar University - Bawadi, Hiba; Shami, Rula; El-Awaisi, Alla; Al-Moslih, Ayad; Abdul Rahim, Hanan; Du, Xiangyun; Moawad, Joyce; Al-Jayyousi, Ghadir Fakhri (Frontiers in Medicine, 2023)
Covid-19 has imposed many shared implications on medical and health education. Just like other health education programs at most institutions, the Qatar University health cluster applied a containment approach and shifted all learning to online and onsite training was replaced by virtual internship (VI) during the first wave of the pandemic. Our study aimed to explore the challenges of virtual internships during the COVID-19 pandemic and their influence on the professional identity of the health cluster students at Qatar University. A qualitative approach was employed. In total, eight focus groups with students (N=41) and 14 semi-structured interviews with clinical instructors from all the health cluster colleges were conducted. Transcripts were analyzed following the inductive approach. The major challenges reported by students were mainly related to the lack of skills needed to navigate the VI, professional and social stressors, the nature of VI and quality of learning, technical and environmental issues, and the development of students’ professional identity in an alternative environment of the internship. The challenges related to the development of professional identity included: limited clinical (practical) experience, lack the experience in fighting the pandemic, lack of communication and feedback, and lack of confidence in meeting the internship’s goals. The findings are important to identify the inevitable barriers to virtual learning for medical students and provide a better understanding of how such challenges and different experiences would be affecting the development of their PI. Hence, students, instructors, and policymakers alike should strive to minimize these barriers. Since physical interactions and patient contact are indispensable components of clinical teaching, these extraordinary times demand innovations involving technology, and simulation-based teaching need to be utilized. There is a need for more studies that are focused on determining and measuring the short and long-term effects of the VI on the students’ PI development.